Bibliometric Analysis of Environmental Law Research: Identification of Thematic Focuses and Global Collaboration Networks - Judijanto, Loso (West Science Law and Human Rights, 2025)
This study does a thorough bibliometric analysis of environmental legal research to ascertain its topic foci, intellectual framework, and global collaboration networks. The study utilizes data from Scopus and Web of Science, employing VOSviewer and Bibliometrix tools to examine publication patterns, keyword co-occurrences, and collaborations among institutions and countries from 2000 to 2025. The findings indicate three primary topic clusters: (1) environmental law and governance, (2) regulation and enforcement, and (3) climate change and sustainable development. The United States, China, and the Netherlands are the primary influential donors, while burgeoning collaborations from Asia and Latin America signify an increasing diversification of worldwide research involvement. Author and institutional networks, including prominent individuals like Heyvaert, Sands, and Peel, exemplify the international and interdisciplinary characteristics of the area. The study highlights the evolution of environmental law into a worldwide and integrated field, integrating legal theory, policy, and sustainable practices. It provides strategic ideas for enhancing collaboration, capacity development, and evidence-based policymaking in environmental governance.